STUDENTS’ PERCEPTION ON THE USE OF ENGLISH SONGS IN AUDITORY LEARNING : LISTENING SKILL - Nurhasanah, Siti Rahmi; Suryaman, Maman (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study is to take a look at how the use of English songs affect students who have an auditory learning style and their perception on the effects, therefore literature review will be used as a method of achieving the purpose of this study. Literature review is done by doing surveys on multiple scholarly sources such as journal articles on a specific matter. Based on the findings throughout this study, there are some aspects to be discussed by the writer. The first aspect is about how different students have different learning styles. People have their own unique learning style and when they are able to identify their own learning style, it is easier for them to include techniques corresponding to their learning style into their learning process. From all the journals that have been reviewed, the most outstanding part found is the fact that music has an enormous impact on learning, especially language learning. It is widely known that classical music increases concentration, but less research is done around the use of foreign songs to learn a foreign language. By understanding the students’ perception on learning, instructors are more capable of creating the correct approach to students. Therefore, it is necessary for instructors to understand the relationship between songs, music, motivation, and learning.